Faktor-Faktor Yang Berhubungan Dengan Kejadian Dismenorea Pada Mahasiswi Fakultas Kedokteran Universitas Bosowa Angkatan 2023: Factors Associated with the Incident of Dysmenorrhea in Female Students of the Faculty of Medicine, Bosowa University Class of 2023 - Bamatraf, Anis; Gloria, Anastasya; Putra, Bayu Pratama (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Dysmenorrhea is defined as a painful, cramping sensation in the lower abdomen that is often accompanied by other symptoms such as sweating, headache, nausea, vomiting, diarrhea, and trembling, all of which occur just before or during menstruation. Dysmenorrhea is one of the many disorders experienced by women during menstruation, pain can occur before menstruation or during menstruation. Pain and anxiety can interfere with activities of daily living. This study aims to determine the factors associated with the incidence of dysmenorrhoea in students at the Faculty of Medicine, Bosowa University Class of 2023. The research method used is analytical observational with a case-control research design. This research was conducted on 54 female students consisting of 27 case samples and 27 control samples. The data used is primary data with the sampling technique used, namely quota sampling. Data were analyzed using the chi-square test and the 95% CI odds ratio test. The results of bivariate analysis showed that there was a relationship between physical activity and the occurrence of dysmenorrhea (p-value = 0.006 and OR = 4,750), there was a relationship between stress levels and the occurrence of dysmenorrhea (p-value = 0.005 and OR = 5,500), there was no relationship between BMI and the occurrence of dysmenorrhea (p-value = 0.056 and OR = 2.909), there is a relationship between the age of menarche and the occurrence of dysmenorrhea (p-value = 0.000 and OR = 15.625). The conclusion of this study is that there is a relationship between physical activity, stress level, and age at menarche with the occurrence of dysmenorrhoea.